Pharmacological Activities of Cilantroʼs Aliphatic Aldehydes against Leishmania donovani - Donega, Mateus A.; Mello, Simone C.; Moraes, Rita M.; Jain, Surendra K.; Tekwani, Babu L.; Cantrell, Charles L. (Planta Medica, 2014)
Leishmaniasis is a chronic infectious disease caused by different Leishmania species. Global occurrences of this disease are primarily limited to tropical and subtropical regions. Treatments are available; however, patients complain of side effects. Different species of plants have been screened as a potential source of new drugs against leishmaniasis. In this study, we investigated the antileishmanial activity of cilantro (Coriandrum sativum) essential oil and its main components: (E)-2-undecenal, (E)-2-decenal, (E)-2-dodecenal, decanal, dodecanal, and tetradecanal. The essential oil of C. sativum leaves inhibits growth of Leishmani donovani promastigotes in culture with an IC50 of 26.58 ± 6.11 µg/mL. The aliphatic aldehydes (E)-2-decenal (7.85 ± 0.28 µg/mL), (E)-2-undecenal (2.81 ± 0.21 µg/mL), and (E)-2-dodecenal (4.35 ± 0.15 µg/mL), all isolated from C. sativum essential oil, are effective inhibitors of in vitro cultures of L. donovani promastigotes. Aldehydes (E)-2-decenal, (E)-2-undecenal, and (E)-2-dodecenal were also evaluated against axenic amastigotes and IC50 values were determined to be 2.47 ± 0.25 µg/mL, 1.25 ± 0.11 µg/mL, and 4.78 ± 1.12 µg/mL, respectively. (E)-2-Undecenal and (E)-2-dodecenal demonstrated IC50 values of 5.65 ± 0.19 µg/mL and 9.60 ± 0.89 µg/mL, respectively, against macrophage amastigotes. These cilantro compounds showed no cytotoxicity against THP-1 macrophages.
Keywords: Coriandrum sativum; Apiaceae; essential oil; (E)-2-decenal; (E)-2-undecenal; (E)-2-dodecenal